DUE TO THE LAW OF SELLING AND BUYING LAND WITH CERTIFICATE OF PROPRIETARY RIGHTS IN UNDER HANDS - Muhammad Azkannasabi (Universitas Muhammadiyah Gresik, 2022)
An underhand deed is a deed that has been made by the parties who made it without being made before an authorized official or it can be called PPAT. The binding power between the seller and the buyer in an underhand deed is the same as an authentic deed. The purpose of this is that it is allowed based on an agreement and does not conflict with the law so that the legal action is indeed legal in accordance with article 1338. The purpose of this study is to analyze and describe the legal protection for buyers against buying and selling land rights that are carried out under the hands. The research conducted in writing this thesis is empirical research, using a sociological juridical approach. Based on the results of the study, it can be concluded that (1) the buyer does not get legal protection for the land he bought; (2) the buyer does not get legal certainty over the land he bought; (3) the buyer does not get strong evidence against the rights to the land he bought. This of course will be detrimental to the buyer who purchases land rights under his own hands. This incident is expected to make people aware of buying and selling before PPAT so that they get legal protection and certainty.